Acquired Hemophagocytic Lymphohistiocytosis Associated With Disseminated Herpes Simplex Virus in Immunocompetent Host. Issue 8 (21st August 2019) - Schwartz, Michael; O'Brien, Courtney; Raya, Nischal; Reau, Nancy
ABSTRACT: We report the case of an immunocompetent young woman who developed multisystem organ failure following herpes simplex virus type 2 and hemophagocytic lymphohistiocytosis. Despite intravenous acyclovir and supportive measures, she rapidly progressed to acute liver failure and died before she could receive orthotopic liver transplant.